SOCIO-ECONOMIC EFFECT OF RESTORING LIVESTOCK LOGISTICS IN THE DEOCCUPIED TERRITORIES (Development Service Industry Management, 2025)
The article identifies the features of the logistics system of the agricultural sector and the factors that influence the formation of logistics supply chains in livestock. It is noted that the restoration of logistics is a direction of management activity in which its provisions and methods are applied in the field of livestock production, considering the challenges and conditions of uncertainty. Such logistics systems combine various areas of the agro-industrial complex, such as animal husbandry, transportation, storage, procurement for feed, processing and sales, and affect the development of related industries. It is this comprehensive understanding of livestock logistics that allows specialists in the agricultural sector to focus their attention on organizing logistics connections directly to ensure agrarian products, considering the specifics of the deoccupied territories of Ukraine.The study substantiates the need to reorient livestock enterprises to implement advanced practices of sustainable development, which will increase the productivity and effectiveness of logistics processes, as well as better meet consumer needs.The criteria for assessing the socio-economic effect of restoring livestock logistics were identified by the main groups of indicators (economic, social and food). The main stages of evaluating such an effect related to the restoration of livestock logistics were determined.The paper also describes the role and importance of organizing the restoration of logistics in livestock farming in the deoccupied territories, which in modern conditions has not only production and economic significance, but also a powerful social impact in the context of regional development. In this regard, the feasibility of correctly understanding the specifics and establishing an assessment of the multiplicative effect of restoring livestock logistics, namely the advantages and difficulties of its implementation within the framework of the regional economy, is proven.
Keywords: livestock; socio-economic effect; logistics restoration; regional development; deoccupied territory; evaluation criteria; logistics chain; added value